Multi-walled carbon nanotube incorporated Nanoporous Titanium Dioxide electrodes for Hybrid Polymer Solar cells - Balashangar, K.; Paranthaman, S.; Thanihaichelvan, M.; Amalraj, P.A.; Velauthapillai, D.; Ravirajan, P. (University of Jaffna, 2018)
This study focuses on incorporating Multi-walled carbon nanotubes (MWNT) in nanoporous titanium dioxides (TiO2) thin film for enhancing the performance of hybrid Poly(3-hexylthiophene)(P3HT)/ TiO2 solar cells. MWNTs were successfully incorporated in the nanoporous TiO2 electrodes either by systematically blending or dipping prior to the deposition of P3HT. Current density–voltage (J-V) characteristic of the corresponding fabricated devices showed that the short-circuit current density (JSC) and fill factor are strongly influenced by the amount of MWNT incorporated into TiO2 nanoparticles. Solar cells with optimum amount of MWNT incorporated by blending in nanoporous TiO2 layer showed a factor of two efficiency enhancement, mainly due to improvement in JSC compared to the corresponding control device. Further increment in MWNT reduces the efficiency mainly due to a sharp drop in fill factor and VOC, which can be attributed to shunting by excess amount of MWNTs. Devices with MWNT dip-coated TiO2 and polymer too showed enhanced efficiency over 2.5% under AM 1.5 illumination (100 mWcm-2), which is a factor of three higher than the corresponding control device.
Keywords: Carbon nanotubes; Electrical properties; Hybrid solar cell; P3HT; TiO2